2021
DOI: 10.3390/biomedicines10010070
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Cytopathic Effects Induced by Influenza, Parainfluenza, and Enterovirus Using Deep Convolution Neural Network

Abstract: The isolation of a virus using cell culture to observe its cytopathic effects (CPEs) is the main method for identifying the viruses in clinical specimens. However, the observation of CPEs requires experienced inspectors and excessive time to inspect the cell morphology changes. In this study, we utilized artificial intelligence (AI) to improve the efficiency of virus identification. After some comparisons, we used ResNet-50 as a backbone with single and multi-task learning models to perform deep learning on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…We have also discovered that in the virus control group, the pecenage of cell viability was the lowest of all groups (Table 5). The low percentage can be due to cytopathic effects (CPE) of the virus (Chen et al 2021). Based on the data, it is obvious that both the peptide and the virus harmed cell livability, but the effect of the virus is much higher.…”
Section: Discussionmentioning
confidence: 99%
“…We have also discovered that in the virus control group, the pecenage of cell viability was the lowest of all groups (Table 5). The low percentage can be due to cytopathic effects (CPE) of the virus (Chen et al 2021). Based on the data, it is obvious that both the peptide and the virus harmed cell livability, but the effect of the virus is much higher.…”
Section: Discussionmentioning
confidence: 99%
“…However, many factors are associated with candidemia‐related mortality, and their correlations can make developing an accurate predictive model challenging. Various machine learning (ML) techniques have been applied in medicine, such as outcome prediction, diagnosis, medical image interpretation, and treatment 22–25 . This study adopted a data‐driven ML approach to candidemia mortality prediction that involves many factors of various types.…”
Section: Introductionmentioning
confidence: 99%
“…Various machine learning (ML) techniques have been applied in medicine, such as outcome prediction, diagnosis, medical image interpretation, and treatment. [22][23][24][25] This study adopted a data-driven ML approach to candidemia mortality prediction that involves many factors of various types. Unlike classical statistical methods typically hindered by large numbers and mixed types of variables, ML can efficiently and effectively explore large and different variables to construct accurate predictive models.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, work by Wang and colleagues showed that DL can be employed for the detection of influenza-induced CPE in MDCK cells 23 . CPE detection by neural networks has also been described for influenza virus, parainfluenza virus, and enterovirus 24 , but experimental conditions were not documented, and the code or dataset is not available, limiting broader useability. Another study proposed that DL can be used for early detection of viral CPE 25 , but this approach requires a specifically trained model for a given cell line, virus, and imaging modality, making it difficult to use.…”
mentioning
confidence: 99%